Intestinal CD4 Depletion in HIV / SIV Infection - Veazey, Ronald S. (Current Immunology Reviews (Discontinued), 2019)
Among the most significant findings in the pathogenesis of HIV infection was the discovery that almost total depletion of intestinal CD4+ T cells occurs rapidly after SIV or HIV infection, regardless of the route of exposure, and long before CD4+ T cell losses occur in blood or lymph nodes. Since these seminal discoveries, we have learned much about mucosal and systemic CD4+ T cells, and found several key differences between the circulating and intestinal CD4+ T cell subsets, both in phenotype, relative proportions, and functional capabilities. Further, specific subsets of CD4+ T cells are selectively targeted and eliminated first, especially cells critically important for initiating primary immune responses, and for maintenance of mucosal integrity (Th1, Th17, and Th22 cells). This simultaneously results in loss of innate immune responses, and loss of mucosal integrity, resulting in mucosal, and systemic immune activation that drives proliferation and activation of new target cells throughout the course of infection. The propensity for the SIV/HIV to infect and efficiently replicate in specific cells also permits viral persistence, as the mucosal and systemic activation that ensues continues to damage mucosal barriers, resulting in continued influx of target cells to maintain viral replication. Finally, infection and elimination of recently activated and proliferating CD4+ T cells, and infection and dysregulation of Tfh and other key CD4+ T cell results in hyperactive, yet non-protective immune responses that support active viral replication and evolution, and thus persistence in host tissue reservoirs, all of which continue to challenge our efforts to design effective vaccine or cure strategies.
Keywords: T-cell